Tofu Goodies: A Strategic Business Plan for the Production and Marketing of Plant-Based Nuggets with Homemade Sauces (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study evaluated the market acceptability and consumer perception of Tofu Goodies—an innovative, plant-based nugget paired with signature homemade sauces—in Barangay Paciano Rizal, Bay, Laguna. Using a descriptive-quantitative research design, data were gathered from 289 purposively selected respondents, primarily composed of students and young professionals aged 18–24 (43.25%) operating on limited budgets. The empirical findings revealed a high level of overall market acceptability (Mean = 3.03), driven primarily by excellent product quality (Mean = 3.10) and an affordable pricing structure ranging from ₱11.00 to ₱55.00 (Mean = 3.06).While respondents highly praised the health benefits (Mean = 3.25) and eco-sustainability (Mean = 3.07) of the product, sensory imitation benchmarks scored lower (Mean = 2.77). Inferential analysis via One-Way ANOVA confirmed no statistically significant difference in product acceptability across diverse demographic cohorts (p > 0.05). Crucially, Pearson correlation analysis revealed no significant relationship between consumer perception and actual market acceptability (r = -0.0186, p = 0.7534), mathematically proving that intellectual appreciation for healthy food does not automatically drive purchasing decisions. Market competition (Mean = 2.87) and localized geographical accessibility (Mean = 2.67) were identified as the primary operational challenges. Based on these insights, a Strategic Marketing Action Plan utilizing a hub-and-spoke distribution model and sensory-focused digital marketing is proposed to optimize business sustainability and local market penetration.